Catechin hydrate prevents cisplatin-induced spermatogonia GC-1 spg cellular damage - Shim, Hyeon Woo; Lee, Won-Yong; Ham, Youn-Kyung; Lim, Sung Don; Hwang, Sun-Goo; Park, Hyun-Jung (Journal of animal reproduction & biotechnology (Online), 2024)
Background: Despite its anticancer activity, cisplatin exhibits severe testicular toxicity when used in chemotherapy. Owing to its wide application in cancer therapy, the reduction of damage to normal tissue is of imminent clinical need. In this study, we evaluated the effects of catechin hydrate, a natural flavon-3-ol phytochemical, on cisplatin-induced testicular injury. Methods: Type 2 mouse spermatogonia (GC-1 spg cells) were treated with 0-100 μM catechin and cisplatin. Cell survival was estimated using a cell proliferation assay and Ki-67 immunostaining. Apoptosis was assessed via flow cytometry with the Dead Cell Apoptosis assay. To determine the antioxidant effects of catechin hydrate, Nrf2 expression was measured using qPCR and CellROX staining. The anti-inflammatory effects were evaluated by analyzing the gene and protein expression levels of iNOS and COX2 using qPCR and immunoblotting. Results: The 100 μM catechin hydrate treatment did not affect healthy GC-1 spg cells but, prevented cisplatin-induced GC-1 spg cell death via the regulation of anti-oxidants and inflammation-related molecules. In addition, the number of apoptotic cells, cleaved-caspase 3 level, and BAX gene expression levels were significantly reduced by catechin hydrate treatment in a cisplatin-induced GC-1 spg cell death model. In addition, antioxidant and anti-inflammatory marker genes, including Nrf2 , iNOS, and COX2 were significantly downregulated by catechin hydrate treatment in cisplatintreated GC-1 cells. Conclusions: Our study contributes to the opportunity to reintroduce cisplatin into systemic anticancer treatment, with reduced testicular toxicity and restored fertility.